(untitled) (Tikrit Journal of Veterinary Science, 2024)
Breast cancer (BC) is the most frequently diagnosed cancer in women worldwide, and it is ranked as second in terms of cancer related death in women. The aim of this study several stem markers have been described for the various histological subtypes of breast cancer, stem cells (CSCs) of breast cancer have been found to strongly express adhesion molecule glycoprotein cluster of differentiation 44 (CD44). CD44 is expressed in the membrane of the cells, so it differs from the other studied markers which were cytoplasmic expressed markers. Negative expression scored (0) were observed in 15 out of 31samples (48.3%), while score (+) found in 5 out of 31samples (16.12%), score (++) found in 2 out of 31samples (6.4%)and score (+++) found in 9 out of 31samples.